The impact of foreign policy on GE14. Issue 2 (3rd March 2020) - Han, David
ABSTRACT: The historic results of the 14th Malaysian general elections (GE14) have largely been attributed to various domestic factors. This paper seeks to address whether foreign policy issues, specifically the rise of China in the Malaysian economy, were a prominent campaign feature in the election. This article argues that while foreign policy issues, including the rise of China in the Malaysian economy, neither featured prominently in GE14 (as it was overshadowed by domestic concerns), nor were the most decisive factor in determining the outcome of the election, the role of foreign affairs in the run-up to GE14 was by no means insignificant. Foreign affairs received much more attention compared to previous elections. Furthermore, as a result of growing democratic space in Malaysia, the Najib administration's foreign policy which was supposedly highly insulated from public scrutiny became increasingly challenged by domestic political opponents.